1976
DOI: 10.1177/028418517601700209
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications following Needle Puncture of the Liver

Abstract: Angiography after liver puncture was performed at different intervals in 51 patients. Fourteen cases had abnormalities believed to be caused by the puncture. Most of these were small but there were also 4 cases with large liver hematomas and 1 case with an abscess between the liver and the abdominal wall, none requiring acute surgery. No certain correlation between the severity of the injury and the diameter of the puncture instrument could be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Vascular defects such as arteriovenous shunts and occluded arteries have also been reported. In 1976, Hellekant showed angiographic defects in 61% of patients within 1 week of biopsy, but in only 11% of angiograms done after one week [14]. Subsequent studies of angiography after percutaneous liver biopsy have shown arteriovenous fistulae, mostly arterioportal, in 5.4%–6.3% of patients within one week to one month of the procedure [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular defects such as arteriovenous shunts and occluded arteries have also been reported. In 1976, Hellekant showed angiographic defects in 61% of patients within 1 week of biopsy, but in only 11% of angiograms done after one week [14]. Subsequent studies of angiography after percutaneous liver biopsy have shown arteriovenous fistulae, mostly arterioportal, in 5.4%–6.3% of patients within one week to one month of the procedure [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“… 1 The indication for active and urgent intervention includes the association of haemobilia, as in our first case. 6 This is due to injury to the portal triad, where portal venules, arterioles, and biliary tract lie nearby. 1 In the absence of haemobilia, the presentation is usually delayed with features of portal hypertension (gastrointestinal bleeding and ascites) or diarrhea (due to congestive vascular enteropathy).…”
Section: Discussionmentioning
confidence: 99%